Magnetic Copper Ferrite Nanoparticles: An Inexpensive, Efficient, Recyclable Catalyst for the Synthesis of Substituted Benzoxazoles via Ullmann-Type Coupling under Ligand-Free Conditions - Yang, Daoshan; Zhu, Xiao; Wei, Wei; Jiang, Min; Zhang, Ning; Ren, Dandan; You, Jinmao; Wang, Hua (Synlett, 2014)
A new sustainable strategy for the synthesis of benzoxazoles from substituted N-(2-halophenyl)benzamides was developed in which inexpensive, readily available, air-stable, recyclable copper(II) ferrite serves as a nanocatalyst. The nanocatalyst can be completely recovered with an external magnet and can be used seven times without significant loss of catalytic activity.
Keywords: nanostructures; catalysts; copper; iron; heterocycles; cyclizations; coupling